A Case Report of Primary Ovarian Mucinous Adenocarcinoma treated at Dr. Akbar Niazi Teaching Hospital, Bara Kahu, Islamabad - Jahan Ara Saeed, Jahan Ara Saeed (Journal of Rawalpindi Medical College, 2023)
Introduction: This is a case of a patient who had a history of grossly increasing abdominal distension for 6 months. The patient had no symptoms except pressure symptoms with a regular menstrual cycle. She initially was investigated as a case of abdominal distension and indigestion. With increasing size, the discomfort was the main symptom. She attended our Gynaecology Outpatient department and was diagnosed as a case of Large Ovarian mass. The first investigation performed was Pelvic ultrasound and Tumour markers and a Risk of malignancy index were calculated. Her Magnetic resonance imaging with contrast showed a large well encapsulated ovarian mass with no ascites and no metastasis. After getting all the investigations and discussion with the patient a Staging Laparotomy with Total abdominal hysterectomy and bilateral salpingo-oophorectomy was performed, The ureters were stented before laparotomy to avoid damage to the ureters during surgery. She was diagnosed as Stage 1-A at the time of surgery and had an uneventful recovery. Her histopathology report showed a unilateral Mucinous cystadenocarcinoma with negative peritoneal wash and omentum histopathology.